Investigating the response mechanisms of the intertidal seagrass Zostera japonica to increased UVB radiation through physiological, transcriptomic, and metabolomic analyses - Jiayi Xin; Song Xue; Hongzhen Wang; Xinqi Li; Yu Zang; Lei Liu; Xuexi Tang; Jun Chen (Ecotoxicology and Environmental Safety)
Global climate change has led to increased ultraviolet-B (UVB) radiation, which is now a major global environmental issue that poses significant threats to ecosystems. Zostera japonica, a higher plant inhabiting the intertidal zone, is particularly impacted by this increase in UVB radiation. Furthermore, its unique evolutionary history has endowed Z. japonica with distinct characteristics that differentiate its response to environmental changes from those of other marine and terrestrial plants. However, the specific response mechanisms of Z. japonica to elevated levels of UVB radiation are not fully understood. Therefore, we investigated the response mechanism of Z. japonica to varying doses of increased UVB radiation by integrating the physiological responses with transcriptomic and metabolomic analyses. The results revealed that excessive reactive oxygen species (ROS) were key substances induced by increased UVB radiation and that photosynthesis was significantly inhibited. To mitigate these adverse effects, the expression levels of genes related to antioxidants and UV-absorbing compounds, including flavonoids (PAL, 4CL, CHS, CHI, F3H) and antioxidant enzymes (DHAR, MDHAR, APX), were upregulated. The increased synthesis of these compounds serves to scavenge accumulated ROS and absorb UV radiation. Notably, flavonoids are the preferred compounds synthesized by Z. japonica, in contrast to other plant species. In addition, the weighted gene coexpression network analysis (WGCNA) method was employed to identify genes that may play important roles in the response of Z. japonica to increased UVB radiation. The results of this study provide new insights into the potential mechanisms of the response of Z. japonica to increased UVB radiation and serve as important references for elucidating the environmental adaptation mechanisms of intertidal seagrasses.